Hardware And Psychological Indicators Of Individual Objectivization Of Psychophysical Abilities Of Youth - Boltivets, Sergei (Զանգակ հրատ.)
The article substantiates the relevance of tempering youth on the psychophysiological basis of identification of a young person in his own self-awareness. Its individual psychological reflection is embodied in the psychophysiological parameters of specially created for this purpose and manufactured psychological devices "Duzhin", "Pyatra", "Rin" and others, which are distinguished by the uniqueness of both the design and the technical implementation. The psychological system "Duzhin" ensures the definition and development of the ability to emotional and volitional self-regulation without age restrictions, as a rule, starting from the age of three - with the acquisition of the ability to imitative reproduction of psychomotor action. Measuring the coefficient of emotional-volitional regulation using the psychological device "Duzhin" allows one to establish the individual dynamics and development of emotional- volitional regulation caused by the development of primary control of impulses - psychomotor processes of brain self-control of one's own activity by periodically determining the variability of its coefficients; to develop the ability for emotional-volitional self-regulation of psychomotor processes of cerebral self-control of one's own activity, to focus the volitional function of the psyche on conscious management of one's own actions and regulation of behaviour, to carry out psychological correction of impulsive behaviour caused by a violation of impulse control. The "Pyatra" device has five main levels of complexity, the mastery of which reveals psychomotor abilities in their creative expression, allows you to go beyond the proposed standard tasks and randomly try to implement your own options for performing psychomotor exercises. "Piatra" contains a subtest for measuring the psychomotor praxis of thinking "Rin for distinguishing indicators of mental development F-70-73, determining related intellectual functioning as a conditional mental norm - related to the sufficiency of mental development, as well as a special mental ability. The indicators recorded in the protocol are given psychological examination according to the scale of the psychomotor praxis of thinking "Rin". The fundamental principle embodied by the above means of objectification of individual self- awareness of psychophysical abilities is the mythologeme of community, which includes everyone and does not reject anyone from the human population commensurate with the possibilities of their own psychophysical development.
Keywords: Psychology